In Situ Monitoring of Stress Developments and Mechanical Integrity during Galvanostatic Cycling of LiCoO2 Thin Films. (9th November 2015) - Malav, Vineet; Jangid, Manoj K.; Hait, Indranil; Mukhopadhyay, Amartya
Abstract : We report here observations made during monitoring of the in-plane stress developments in situ during electrochemical cycling of c-axis oriented LiCoO2 thin film electrodes. Delithiation in the single phase regime leads to monotonic buildup of stresses, with the recorded magnitudes agreeing fairly well with that expected based on the respective contraction of the a-axis dimensions. On the contrary, the overall stresses cease to buildup, followed by signatures of stress release, during the regime corresponding to the co-existence of two phases. Our observations, along with preliminary analysis/estimations, suggest that mechanical degradation takes place primarily during the phase transformations.